Differentiation of Antemortem and Postmortem Appendicular Fractures Using Magnetic Resonance Imaging Signal Intensity Changes in Bone and Soft Tissues,. Issue 5 (11th June 2020) - Oetelaar, Garrett; Heng, Hock Gan; Lim, Chee Kin; Cox, Abigail; Weng, Hsin‐Yi
Abstract: Intraosseous T1‐weighted (T1W) and short‐tau inversion recovery (STIR) magnetic resonance imaging (MRI) signal intensity changes—so‐called bone marrow edema—may be able to differentiate antemortem and postmortem fractures in human forensic imaging. The primary objective of this study was to investigate this hypothesis using an animal model. Three juvenile Landrace pigs were anesthetized and underwent MRI of both tibiae and both radii using a 1.5 T magnet. T1W, T2‐weighted (T2W), STIR, and T2* sequences were included. Antemortem fractures were induced in both tibiae and postmortem fractures in both radii, and MRI was repeated. Two board‐certified radiologists blinded to fracture group jointly evaluated the images for intraosseous and soft tissue signal intensity changes. Sensitivity (Se) and specificity (Sp) in identifying antemortem fractures were calculated based on intraosseous, soft tissue, and combined intraosseous and soft tissue signal intensity changes. Intraosseous and soft tissue signal intensity changes, when present, were hyperintense in all sequences. Intraosseous hyperintensity in T1W and T2W sequences yielded Sp of 100% for antemortem fractures. Regardless of sequence, soft tissue hyperintensity was comparatively more sensitive than intraosseous hyperintensity. Sensitivity for each sequence could be maximized by assessment of soft tissue and intraosseous hyperintense signals together; for the T1W sequence, such assessment optimized diagnostic utility yielding a Se of 100% and Sp of 83%. In summary, MRI—particularly the T1W sequence—can differentiate antemortem and postmortem fractures and may be a useful adjunct to the forensic analyses of fractures.